The development of islamic corporate social responsibility (I-CSR) disclosure index / Azlan Md. Thani …[et al.] - Md. Thani, Azlan; Ahmad, Mohd. Azmi Nias; Amat, Mohd. Aripin; Hashim, Azizi (2016)
This paper attempts to discuss the importance need to extend the corporate social reporting with Islamic values, ethics and principles to ensure that the shariah-approved companies (SACs) are act accordance to shariah law. Consequently it will help the relevant stakeholders to evaluate the level of accountability and transparency of SACs from the eyes of Islamic perspectives. As Malaysia is targeting to become international hub for Islamic finance and halal industry, the inclusion of Islamic values in the report of SACs in Malaysia need to be improvised.